Diplomacy and the religious question: Mazarin, Cromwell and the treaties of 1655 and 1657 - David L. SMITH (E-REA)
This paper explores the diplomatic negotiations that led up to the two treaties between Cardinal Mazarin and Oliver Cromwell in November 1655 and March 1657, and that then surrounded the operation of that alliance in practice until Cromwell’s death in September 1658. The paper examines the dilemmas of two leaders of different faiths, who negotiated with each other despite their religious differences, and who ultimately achieved a sometimes tense but nonetheless workable alliance. As such, it offers a case-study of the issues and challenges that faced cross-cultural and cross-confessional diplomacy in mid-seventeenth-century Europe.